Externally Triggered Novel Rapid-Release Sonosensitive Folate-Modified Liposomes for Gemcitabine: Development and Characteristics - Omar MM (Dove Medical Press, 2021)
Mahmoud M Omar,1,2 Omiya Ali Hasan,1,2 Randa Mohammed Zaki,3,4 Nermin E Eleraky5 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Deraya University, Minia, 61768, Egypt; 2Department of Pharmaceutics and Clinical Pharmacy, Faculty of Pharmacy,Sohag University, Sohag, 82524, Egypt; 3Department of Pharmaceutics, Faculty of Pharmacy, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 4Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Beni-Suef University, Beni-Suef, Egypt; 5Department of Pharmaceutics, Faculty of Pharmacy, Assiut University, Assiut, 71526, EgyptCorrespondence: Mahmoud M OmarDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Deraya University, Deraya Square Street, Minia, 61768, EgyptTel +20 10 0933 2419Email mahmoudmomar@hotmail.comPurpose: To develop an externally triggered rapid-release targeted system for treating ovarian cancer, gemcitabine (GMC) was entrapped into sonosensitive (SoS) folate (Fo)-modified liposomes (LPs).Methods: GMC-loaded LPs (GMC LPs), GMC-loaded Fo-targeted LPs (GMC-Fo LPs), and GMC-loaded Fo-targeted SoS LPs (GMC-SoS Fo LPs) were prepared utilizing a film-hydration technique and evaluated based on particle size, ζ-potential, and percentage entrapped drug. Cellular uptake of the fluorescent delivery systems in Fo-expressing ovarian cancer cells was quantified using flow cytometry. Finally, tumor-targeting ability, in vivo evaluation, and pharmacokinetic studies were performed.Results: GMC LPs, GMC-Fo LPs, and GMC-SoS Fo LPs were successfully prepared, with sizes of < 120.3± 2.4 nm, 39.7 mV ζ-potential, and 86.3%± 1.84% entrapped drug. Cellular uptake of GMC-SoS Fo LPs improved 6.51-fold over GMC LPs (under ultrasonic irradiation — p< 0.05). However, cellular uptake of GMC-Fo LPs improved just 1.24-fold over GMC LPs (p> 0.05). Biodistribution study showed that of GMC concentration in tumors treated with GMC-SoS-Fo LPs (with ultrasound) improved 2.89-fold that of free GMC (p< 0.05). In vivo, GMC-SoS Fo LPs showed the highest antiproliferative and antitumor action on ovarian cancer.Conclusion: These findings showed that externally triggered rapid-release SoS Fo-modified LPs are a promising system for delivering rapid-release drugs into tumors.Keywords: sonosensitive liposome, gemcitabine, folate-modified liposomes, externally triggered, ovarian cancer